The Emergence of Narrative and the Discovery of Humanism: Curriculum and Research Lessons from the Italian Renaissance - Kushner, Saville (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
This paper returns to the roots of European Humanism to rediscover the moral and political base for contemporary narrative inquiry. A brief analytical review is conducted of forms of artistic representation from C15th/C16th Florentine painting to reveal steps taken to use narrative form in the pursuit and advocacy of humanist method. This is placed within the frame of a Ricoeur (1989) four-stage typology for narrative method. The paper closes with an argument that social and educational research should be guided by Humanist principles in its aims, but also in its method – Humanist in intent, Humanist in substance.